Respuesta :

It is important to know that a Product is the result of a multiplication.

You have the following expression given in the exercise:

[tex]\mleft(3y+1\mright)\mleft(3y-1\mright)​[/tex]

Notice that it is the multiplication of two Binomials and it has this form:

[tex](a+b)(a-b)[/tex]

By definition:

[tex](a+b)(a-b)=a^2-b^2[/tex]

This is called "Difference of two squares".

You can identify that, in this case:

[tex]\begin{gathered} a=3y \\ b=1 \end{gathered}[/tex]

Therefore, you get:

[tex]\mleft(3y+1\mright)\mleft(3y-1\mright)​=(3y)^2-(1)^2=9y^2-1[/tex]

The answer is:

[tex]9y^2-1[/tex]